DETERMINANTS OF THE ECONOMY IN ORGANIZATION OF ISLAMIC COOPERATION (OIC) COUNTRIES FROM 1991 TO 2015 - Brilly Artsilia Prisaris Isrofil; Raditya Sukmana (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This research aimed to discover the influence of government expenditure, unemployment, and minimum wage of OIC’s member countries on the economy. This research used data by the World Bank with a quantitive approach and were analyzed by using panel data analysis. According to the result, government expenditure, unemployment, and minimum wage have a significant influence on the economy (GDP) in the OIC Countries. Government expenditure significantly affects the decreasing of the economy in the OIC Countries. On the other hand, unemployment significantly affects the decreasing of the economy in The OIC countries. And minimum wage significantly affects the increasing of the economy in The OIC Countries.Keywords: OIC, GDP, government expenditure, unemployment, minimum wage.REFFERENCE Ahmad, Khursid. (1997). Pembangunan ekonomi dalam perspektif islam, dalam etika ekonomi politik. Jakarta: Risalah Gusti.Alghofari, Farid. (2010). Analisis tingkat pengangguran di indonesia tahun 1980-2007. Junal Pengangguran, 1(1).Baltagi, Badi H. (2008). Econometrics. USA: Springer.Baltagi, Badi H. (2005). Econometric analysis of panel data. England: John Wiley & Sons.Barro, Robert J. (1989). A cross-country study of growth, saving, and government. Working Paper No. 2855. Barro, Robert J., (1990). Government spending in a simple model of endogenous growth. Journal of Political Economy, 98(5), 103-125.Ghura, Dhaneswar. (1995). Macro policies, external forces, and economic growth in sub-saharan Africa. Economic Development and Cultural Change.Lindauer, D.dan A. Valenchik. (1992). government spending in developing countries: trends, causes and determinants. World Bank Research Observer, 7(1), 59-78.Obeng, Samuel Kwabena. (2015). An empirical analysis of the relationship between minimum wage, investment and economic growth in Ghana. African Journal of Economic Review, 3(2).Sugiyono, (2014), Metode penelitian kuantitatif kualitatif dan R&D. Bandung: Alfabeta.Tello, Claire Larzen Zamora. (2015). Determinants of unemployment rate in selected ASEAN (Association of Southeast Asian Nation) member state: a panel data analysis. Leyte: Visayas State University.Mankiw, N. Gregory. (2006). Makroekonomi edisi keenam. terjemahan oleh Fitria Liza dan Imam Nurmawan. Jakarta: Erlangga.Panjawa, Jihad Lukis dan Daryono Soebagiyo. (2014). Efek peningkatan upah minimum terhadap tingkat pengangguran. Jurnal Ekonomi dan Studi Pembangunan, 15(1).Qazi, Wasim, dkk. (2017). Higher education development and unemployment in Pakistan: evidence from structural break testing. Global Business Review. Sage Publication.Widarjono, Agus. (2013). Ekonometrika: pengantar dan aplikasinya. Jakarta: Ekonosia.